Comprehensive Management of Secondary Craniofacial Deformities in Adult Patients with Congenital Cleft Lip and Palate: Clinical Challenges and Therapeutic Strategies - Sokolovskiy, В. А.; Burkland, К. С.; Kornienko, Л. І. (Actual Dentistry, 2025)
Relevance of the problem. Congenital non-union of the upper lip and palate ranks second in the world among all congenital anomalies in newborns (according to the WHO, CDC (USA), and the European EUROCAT registry). Depending on the region, it occurs in one case per 400 to 1,500 newborns. In Ukraine, on average, one child is born per 650 newborns. Congenital developmental anomaly is accompanied by primary (before surgical interventions) and secondary deformations (after their implementation). Primary deformations are formed in utero and consist of the displacement of unfused fragments of the alveolar process of the upper jaw and horizontal plates of the palatine bone under the influence of the tongue. Secondary deformities are formed after birth under the influence of the nipple, scar-deformed upper lip, and palate after surgical operations. They primarily manifest as sagittal, transverse, and vertical deformities of the upper jaw. Their severity depends, firstly, on the technique of surgical manipulations and the amount of scarred tissues, which are the root cause of secondary deformities. According to the AMERICAN ASSOCIATION OF ORTHODONTICS, the first signs of postoperative sagittal displacement of the upper dentition after cheiloplasty appear after 3 months. Transverse deformation in the form of narrowing of the upper jaw begins to form 6 months after uranostaphyloplasty, and more pronounced manifestations appear after 2–4 years. Vertical secondary anomalies develop more slowly, typically 12–14 months after surgical interventions. The intensity of secondary malocclusions depends primarily on the techniques of plastic surgery and the age at which they are performed (EUROCLEFT, 2001). The most favorable situation is when, after surgical interventions, cicatricial deformation of the jaw is absent or minimal. However, if its development is not monitored and prevented, complex malocclusion problems may arise, which are difficult to cure by orthodontic means. Sagittal displacements in combination with vertical dentoalveolar elongation are particularly complex. The presence of complex deformations in various areas of the maxillofacial region does not allow for a fully standardized treatment protocol for such patients, requiring an individualized approach to their solution by doctors of multiple specializations using the most modern technologies. Purpose: to assess the effectiveness of a comprehensive approach in the treatment of secondary deformations of soft and hard facial tissues using non-standard methods and modern technologies.